Meningococcal carriage in children and young adults: a cross-sectional and longitudinal study, Iceland, 2019 to 2021 - Kristinsdottir, Iris; Visser, Linda J; Miellet, Willem R; Mariman, Rob; Pluister, Gerlinde; Haraldsson, Gunnsteinn; Haraldsson, Asgeir; Trzciński, Krzysztof; Thors, Valtyr (Euro surveillance : bulletin européen sur les maladies transmissibles, 2023)
Background Neisseria meningitidis is a commensal bacterium which can cause invasive disease. Colonisation studies are important to guide vaccination strategies. Aim The study's aim was to determine the prevalence of meningococcal colonisation, duration of carriage and distribution of genogroups in Iceland. Methods We collected samples from 1 to 6-year-old children, 15–16-year-old adolescents and 18–20-year-old young adults. Carriers were sampled at regular intervals until the first negative swab. Conventional culture methods and qPCR were applied to detect meningococci and determine the genogroup. Whole genome sequencing was done on groupable meningococci. Results No meningococci were detected among 460 children, while one of 197 (0.5%) adolescents and 34 of 525 young adults (6.5 %) carried meningococci. Non-groupable meningococci were most common (62/77 isolates from 26/35 carriers), followed by genogroup B (MenB) (12/77 isolates from 6/35 carriers). Genogroup Y was detected in two individuals and genogroup W in one. None carried genogroup C (MenC). The longest duration of carriage was at least 21 months. Serial samples from persistent carriers were closely related in WGS. Conclusions Carriage of pathogenic meningococci is rare in young Icelanders. Non-groupable meningococci were the most common colonising meningococci in Iceland, followed by MenB. No MenC were found. Whole genome sequencing suggests prolonged carriage of the same strains in persistent carriers.